"that every feather is a pen, but living, / / flying" Desire: The Metapoetics of Don McKay's BIRDING, or desire - Bondar, Alanna F. (Studies in Canadian Literature, 1994)
In Don McKay's BIRDING, or desire, the motif of flight and migration serves as an elaborate metaphor for the poetic process. The text discusses its own making: through the metaphor of birding, McKay addresses the nature of poets, the poetic process, and the poet-reader dynamic. Although McKay's poetics critique his own ability to transcribe life's realities into language, the poet must use words (translations of things) to reconstruct a way of responding to the natural world; the artist perpetually (re)creates the world for the reader.